Authenticity as a corporate social responsibility platform for building customer loyalty - Sri Gunawan (Taylor & Francis Group, 2020)
Consumers’ views of corporate social responsibility (CSR) are still filled with mistrust and doubt. Especially in developing countries like Indonesia, consumers are wondering about the motivation behind CSR activities. It is argued that CSR activities that are authentic or sincere will lead to customer loyalty. This research aims to expand the line of studies based on CSR-loyalty, through the concept of sincerity motivating Corporate Social Responsibility activities. Therefore, field research was conducted to investigate whether CSR Authenticity affects Corporate Image, Corporate Credibility and Customer Loyalty among Indonesian consumers. The proposed model was examined using questionnaire with a data set of 257 valid responses. Statistical analysis was based on PLS-SEM approach with the use of Smart PLS 3.0. Findings showed that the hypothesis associated with the relationship between Corporate Image and Customer Loyalty was supported. The relationship between Corporate Credibility and Customer Loyalty was also supported; however, the relationship between CSR Authenticity and Customer Loyalty was not supported. Result further showed a mediating effect of Corporate Image and Corporate Credibility on the relationship between CSR Authenticity and Customer Loyalty. Finally, the findings of this study are used to advance managerial implications of CSR Authenticity as a strategic activities of companies in creating its customer loyalty.